Single-cell RNA sequencing data on primary samples from: Aberrant expression of SLAMF6 constitutes a targetable immune escape mechanism in acute myeloid leukemia - Sandén, Carl; Lilljebjörn, Henrik; Fioretos, Thoas (Lund University, 2025)
This dataset includes single-cell RNA sequencing (scRNA-seq) data from primary AML (acute myeloid leukemia) samples. Libraries were produced using the 10X Genomics Chromium Single Cell 3ʹ Reagent Kits v3 and sequenced on an Illumina Novaseq 6000 system (Illumina). The dataset is available as raw sequencing reads (fastq; restricted access) or as an annotated matrix of scRNA count data (h5ad). Published in: Sandén et al, Nature Cancer, 2025: https://www.nature.com/articles/s43018-025-01054-6
Keywords: Cancer cell biology; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi